If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + x = 2(x + -5) Reorder the terms: 4 + x = 2(-5 + x) 4 + x = (-5 * 2 + x * 2) 4 + x = (-10 + 2x) Solving 4 + x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 4 + x + -2x = -10 + 2x + -2x Combine like terms: x + -2x = -1x 4 + -1x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 4 + -1x = -10 + 0 4 + -1x = -10 Add '-4' to each side of the equation. 4 + -4 + -1x = -10 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = -10 + -4 -1x = -10 + -4 Combine like terms: -10 + -4 = -14 -1x = -14 Divide each side by '-1'. x = 14 Simplifying x = 14
| 4(x+1010)=3(x-10101) | | 44-x=11 | | n+3.7=9.8 | | 2-5[x+3(x+7)]= | | 7x-31=-25 | | 8.5t=83.30 | | 4x-0=1 | | -23682-6k=6+18k | | 6x(x-9)=13x^2-55x | | 10x+7=-x-15 | | 5x=234 | | 8z=9z-3 | | 7+3t-1=8t+24-2t | | 2[4-9x]=9x+7 | | -143=3(-6b-1)+4 | | 6(5y-8)-(7y+4)= | | 9x^2+13=247 | | -4(1-5v)=-144 | | 7+5[1+2(2x+5)]=6(x+7) | | P-16=13-6p | | 4c+1-c=19 | | (x+5)(x-2)=35 | | 8b-5b-7=23 | | 8y+4y=144 | | 2.5[x+3(x+7)]= | | 6x+8y=-11 | | (3a)+(2a-25)=180 | | .50(x-2)=4x-0.2222x-4 | | 5(3b-4)=40 | | 3(4x+3)=17 | | 6r+5=4(r+2)-2r | | 2yf-3(2y-3)+2=31 |